2018
DOI: 10.3791/56804
|View full text |Cite
|
Sign up to set email alerts
|

Treating Low Back Pain in Failed Back Surgery Patients with Multicolumn-lead Spinal Cord Stimulation

Abstract: Failed back surgery syndrome (FBSS) refers to persistent, chronic pain following spinal surgery. Spinal cord stimulation with dorsal epidural leads can be used to treat back and leg pain in FBSS patients. This paper presents a detailed protocol for using spinal cord stimulation with surgical leads in FBSS patients. In our department, with the patient under general anesthesia, we place the lead in the epidural space by means of a small laminectomy at the 10 thoracic level. Placement of the lead is followed by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Moreover, a case control study showed that the use of SCS in patients with FBSS was associated with reduced sick leave and disability pension [22]. Another retrospective analysis on the use of healthcare resources in over 120,000 FBSS patients with a follow-up of up to 9 years, showed improved long-term health economics to support the long-term cost utility of SCS [23][24][25][26]. The success rate of SCS for these two conditions is higher in patients who are treated within one year after their last unsuccessfull spine surgery [19].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a case control study showed that the use of SCS in patients with FBSS was associated with reduced sick leave and disability pension [22]. Another retrospective analysis on the use of healthcare resources in over 120,000 FBSS patients with a follow-up of up to 9 years, showed improved long-term health economics to support the long-term cost utility of SCS [23][24][25][26]. The success rate of SCS for these two conditions is higher in patients who are treated within one year after their last unsuccessfull spine surgery [19].…”
Section: Discussionmentioning
confidence: 99%
“…Closed loop SCS was also introduced to mitigate the effects of positional changes and the development of tolerance [80]. A new SCS paradigm has also been developed with a 3-dimensional anatomical model of the spinal cord automatically calculating the optimal program to precisely target the selected central point of stimulation [81,82]. The use of SCS is limited due to the high cost of the stimulators.…”
Section: Main Bodymentioning
confidence: 99%